Physicochemical and Microbial Assessment of Selected Borehole Water in Ogwashi-Uku, Delta State, Nigeria - Ofuani, Amalachukwu Grace; Destiny, Edward C. (IPS Journal of Applied Microbiology and Biotechnology, 2022)
The assessment of the quality of water samples from Ogwashi-Uku, Delta State of Nigeria was conducted to determine the suitability of these borehole water samples. Three samples of borehole water obtained from three different areas in Ogwashi-Uku were analyzed for physiochemical heavy metals and microbial parameters using standard analytical method of APHA (1998). The results of microbial analysis revealed that total coli form count (0.00CFU/100ml) and Escherichia coli (0.00CFU/100ml) were not present in all the water samples analyzed showing that they were within the stipulated standard by WHO (2011). The physiochemical analysis showed that all the samples met the recommended standard except for pH (6.00-6.60) which fell below the range of 6.5-8.5 of WHO standard. From the heavy metals; lead and zinc were only detected in Mega Chi’s place water samples with a value of 0.10mg/l for each, cadmium was detected in all the water samples ranging from 0.01mg/l – 0.02mg/l, while copper and nickel were below detectable limit in all the water samples analyzed. This shows that the heavy metals were all within the stipulated limit set by WHO (2011). The depth of the borehole in relation to the distance of the septic tank and distance of refuse dump as obtained from these areas revealed that all the samples are very far apart from the refuse dump and the depths was according to the regulatory standard of 150ft standards and is safe for drinking and for other domestic purposes.